Surgical Principles of Minimally Invasive Procedures : Manual of the European Association of Endoscopic Surgery (EAES) - Bonjer, H. Jaap (Springer International Publishing : Imprint: Springer, 2017)
This book provides surgeons and surgical residents with the best practical knowledge currently available on commonly performed minimally invasive abdominal and thoracic procedures. Expert European surgeons share their career-long experience by doing a step-by-step dissection of operative procedures, and highlighting potential technical and anatomical hazards. Uniform full color illustrations complete the detailed descriptions of minimally invasive surgeries. In addition to the operative instructions, Surgical Principles of Minimally Invasive Procedures provides information on patient selection, choice of operative approach, special needs for minimally invasive procedures, and the early diagnosis and treatment of complications after surgery. .
Keywords: Medicine.; Abdominal surgery.; Minimally invasive surgery.; Pediatric surgery.; Thoracic surgery.; elektronické knihy; electronic books